Panorama de acesso a plantas medicinais e a fitoterapia na atenção primária à saúde no município de Mineiros-GO - Batista, Marina Ressiore (Universidade do Vale do Rio dos Sinos, 2018)
In 1972, at the International Conference on Primary Health Care, WHO recognized the use of herbal and medicinal plants as a therapeutic option and recommended the diffusion and insertion of phytotherapy into Primary Health Care (PHC) programs. The Unified Health System (UHS) indicates phytotherapy as an integrative and complementary therapy to health and proposes specific policies and regulations of this practice. It is a field research, carried out between 2017 and 2018, in the primary care of the municipality of Mineiros-GO, aiming to point out the medicinal and phytotherapeutic plants most frequently used by PHC users, as well as those most prescribed by the professionals and also highlight the interest of managers in facilitating and expanding access to these therapies. It is possible to evaluate the main difficulties encountered by the prescribers regarding the indication of these drugs, relating them to the year and model of training, personal interest in the subject and availability to participate in workshops promoted from the data listed. With regard to the users, it is possible to know the profile of age, schooling and frequency of use, besides the interest that these therapies are available in the basic network for consumption. Among the managers, there was concern about the cost of programs that value medicinal plants and herbal medicines, even with the advent of PIC`S, indicating a shortage of financing. Didactic material was elaborated at the end of the study with the purpose of reaching two publics, users and prescribers, clarifying doubts and pointing out more used medicines in our region.
Keywords: Plantas medicinais; Fitoterapia; Atenção básica; Medicinal plants; Phytotherapy; Basic care; ACCNPQ::Ciências da Saúde::Nutrição